PENGARUH PENERAPAN MODUL STILES BIOLOGI SEL TERHADAP PENINGKATAN HASIL BELAJAR MAHASISWA PADA ANGKATAN 2015 JURUSAN PENDIDIKAN BIOLOGI FAKULTAS TARBIYAH DAN KEGURUAN UIN ALUDDIN MAKASSAR - Hamansah Hamansah; Hading Hading (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2016)
This study is a Quasi Experiment because this research has not fully controlled for factors internal and external research. Two rombel student of biology and biological ½ ¾ given application module system STLeS Biology Sel. The research location is housed in the building Tarbiyah and Teaching UIN Alauddin Makassar. This study aims to (1) determine student results before taught using Stiles modules Cell Biology Department of Biology Education class of 2015; (2) determine student results after Stiles taught using modules Cell Biology Department of Biology Education class of 2015; (3) the effect of the application of Cell Biology Stiles module to the learning outcomes of students in the class of 2015 the Department of Biology Education. The population in this study were all students of biology class biology ½ and ¾, the semester consisting of two classes or four groups. In this study, there were 75 people population, so that everything becomes the study sample consisted of two study groups. Each of the two study groups are learning to use the module Stiles Biology Sel. The results showed that (1) the results of student learning cell biology before taught using Stiles Module Cell Biology is an average of 49.24; (2) The study of cell biology students after being taught using Stiles Module Cell Biology is an average of 85.72; (3) Module Cell Biology Stiles affect the improvement of student learning outcomes biology education class of 2015. It can be seen from the analysis parameter estimation value sig. count (0,000) <sig. table (0.05). So the hypothesis was accepted because the significance value calculated is less than the significance of the table